Analisis Persepsi Dan Perilaku Terhadap Loyalitas Penggemar Dewa19 Di Restoe Boemi Bandung - Suci Puspita Sari (CV. ITTC INDONESIA, 2025)
This study attempts to analyze Dewa19 fan loyalty within the context of their interactions with a meaningful physical space, the Restoe Boemi restaurant in Bandung. Based on the phenomenon of music fan loyalty that extends beyond music consumption and concerts, this study explores fans' perceptions of Dewa19 as a symbol of closeness, the forms of loyalty behavior they exhibit at Restoe Boemi, and the factors influencing that loyalty. Using a descriptive qualitative approach, data were collected through in-depth interviews with informants who are Dewa19 fans and have visited Restoe Boemi. The results indicate a strong emotional attachment between fans and Dewa19, reflected in their personal experiences with the band's songs and the thematic atmosphere created by the restaurant. Restoe Boemi is interpreted as a space of nostalgia, a form of respect, and part of fan rituals. Loyalty is demonstrated through regular visits, merchandise purchases, and the perception of the restaurant as a must-visit destination for true fans. Fan loyalty is multidimensional and crosses demographic boundaries, with initial engagement influenced by family, friends/partners, and an interest in Dewa19's music. Most of the informants had attended concerts, actively followed the band on social media, and had visited Restoe Boemi more than once. Key factors driving loyalty included the restaurant's atmosphere, nostalgic experiences, fan community, and a symbol of identity. These findings confirm that Restoe Boemi is not only a business entity but also a cultural space that strengthens emotional bonds and drives affective and behavioral loyalty among Dewa19 fans.